The Relationship Between Adolescent Knowledge Level and Potential Side Effects of Using Non-BPOM Skincare Packages Sold on Social Media - Tri Widiastuti; Endang Setyowati; Intan Adevia Rosnarita (Advances in Healthcare Research, 2026)
Purpose: This study aims to describe respondent characteristics and examine the relationship between adolescents’ knowledge levels and the potential side effects of using non-BPOM skincare packages purchased through social media. Research Method: A quantitative observational-analytical study with a cross-sectional design was conducted among 100 adolescent girls aged 13–18 years in Demak Regency, Central Java. Respondents were selected through purposive sampling. Data were collected using validated and reliable structured questionnaires measuring knowledge and potential skincare side effects. Univariate analysis and Fisher’s Exact Test at a 5% significance level were performed using IBM SPSS Statistics. Results and Discussion: Most respondents had good knowledge (91%), while 56% experienced moderate side effects and 43% experienced mild side effects. Fisher’s Exact Test produced a p-value of 1.000, indicating no significant relationship between knowledge level and potential side effects. Product ingredients, skin sensitivity, usage frequency, and product suitability may better explain the reported reactions. Implications: Health professionals, schools, and regulators should strengthen education emphasizing behavioral change, BPOM registration verification, and safe product selection. Future studies should examine product composition, usage behavior, and skin characteristics. Originality: This study specifically investigates knowledge and side effects among adolescents using non-BPOM skincare packages obtained through social media.